(untitled) (World Bulletin of Public Health, 2022)
In the state of radiation, the differential diagnosis of systemic lupus erythematosus and HIV infection is related to the similarity of the clinical picture and etix diseaseThe resulting viral particles attack new cells, causing cell death and disrupting their interaction with other cells, leading to progressive changes in immunity - immunodeficiency. As a result of the immune shifts, resistance to secondary infections and neoplasms is reduced. In addition, due to direct cytotoxic action or as a result of indirect action (autoimmune mechanisms) the cells of the nervous system, blood, cardiovascular, musculoskeletal, endocrine and other systems may be affected. The pathological processes caused by HIV are superimposed on a wide range of changes caused by secondary diseases that have developed against a background of progressive immunodeficiency. All this leads to multiple organ involvement and a variety of clinical symptoms of HiV infection, bringing it closer to systemic diseases of connective tissue, especially systemic lupus erythematosus (SLE)